Optical mapping of cAMP signaling at the nanometer scale - Bock, Andreas (Cell, 2020)
Cells relay a plethora of extracellular signals to specific cellular responses using only a few second messengers, such as cAMP. To explain signaling specificity, cAMP-degrading phosphodiesterases (PDEs) have been suggested to confine cAMP to distinct cellular compartments. However, measured rates of fast cAMP-diffusion and slow PDE-activity render cAMP compartmentalization essentially impossible. Using fluorescence spectroscopy, we show that – contrary to earlier data – cAMP at physiological concentrations is predominantly bound to cAMP binding sites and, thus, immobile. Binding and unbinding results in largely reduced cAMP dynamics which we term ‘buffered diffusion’. With a large fraction of cAMP being buffered, PDEs can create nanometer-sized domains of low cAMP concentrations. Using FRET-cAMP nanorulers we directly map cAMP gradients at the nanoscale around PDE molecules and the areas of resulting downstream activation of cAMP-dependent protein kinase (PKA). Our study reveals that spatiotemporal cAMP signaling is under precise control of nanometer-sized domains shaped by PDEs that gate the activation of downstream effectors.